(untitled) (Asian Journal of Plant Biology, 2014)
Vegetables are major source of heavy metals contaminant in the diet of humans. Currently, monitoring of heavy metals in vegetables is carried out by instruments such as Inductively- Coupled Plasma Optical Emission Spectrophotometer (ICP-OES) or Flow Injection Mercury System (FIMS). Instrumental method alone is costly, need skilled personnel and time consuming. In this work, the papain assay was used to screen for the presence of heavy metals in tweleve digested vegetables samples after neutralization. None of the non-spiked samples tested shows levels of heavy metals above the maximum residue limit (MRL) allowed for heavy metals in vegetables using both instrumental and papain assay. The papain assay was able to detect by mercury-spiked vegetable samples indicating that the assay could tolerate the high salt of the digested sample matrix. Papain assay is simple, rapid and low in cost. It requires small sample volumes and could be carried out in a microplate format. The assay can act as a preliminary screening assay. Positive samples are sent for heavy metals level using instruments. Using this approach, higher frequency and number of monitoring can be carried out.